Resistance to diet-induced obesity in mice globally overexpressing OGH/GPB5 - Macdonald, Lynn E. (National Academy of Sciences, 2005)
We identified a glycoprotein hormone β-subunit (OGH, also called GPB5) that, as a heterodimer with the α-subunit GPA2, serves as a second ligand for the thyroid-stimulating hormone receptor. Mice in which the OGH gene is deleted (OGH(-/-)) are indistinguishable from WT littermates in body weight, response to high-fat diet, metabolic parameters, body composition, and insulin tolerance. Mice engineered to transgenically globally overexpress OGH (OGH-TG) develop ≈2-fold elevations in their basal thyroid levels and weigh slightly less than WT littermates despite increased food intake because of an increase in their metabolic rates. Moreover, when OGH-TG mice are challenged with a high-fat diet, they gain significantly less weight and body fat than their WT littermates. The OGH-TG mice also have reduced blood glucose, insulin, cholesterol, and triglycerides. In contrast to other approaches in which the thyroid axis is activated, OGH-TG mice exhibit only minor changes in heart rate and blood pressure. Our findings suggest that constitutive low-level activation of the thyroid axis (via OGH or other means) may provide a beneficial therapeutic approach for combating diet-induced obesity.